Penerapan Aplikasi Telunjuk Sakti Dalam Pelayanan Administrasi Di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Wonogiri - Zanana Utamy (JIKAP (Jurnal Informasi dan Komunikasi Administrasi Perkantoran), 2021)
This type of research is qualitative descriptive with a case study approach. The research was conducted at Department Of Population And Civil Registration Of Wonogiri Regency. Research data is obtained from informants, events, documents with purposive and snowball sampling. Data collection techniques with observations, interviews and documents. The validity of the data is obtained by triangulating sources and method. Data analysis techniques use interactive model data analysis with stages: 1) data reduction, 2) data presentation, and 3) draw conclusions. As for research procedures with the following steps: 1) the preparation stage, 2) the implementation stage, and 3) the final stage.The result of this research is: 1) the implementation of the Telunjuk Sakti application at the Population and Civil Registration Office of Wonogiri Regency includes: a) Planning for the Telunjuk Sakti application, b) Socialization of the application of the Telunjuk Sakti application, c) Implementation of the Telunjuk Sakti application, d) Results and evaluation of the application of the Telunjuk Sakti application. 2) the implementation of the Telunjuk Sakti application at the Population and Civil Registration Office of Wonogiri Regency has several obstacles including: a) blank spot area, b) inadequate facilities and infrastructure, c) Information Technology capabilities of human resources are still lacking, and d) Telunjuk Sakti application server often has problems, and, 3) erfforts to overcome the obstacles that occur include: a) installing internet network amplifiers, b) making budget proposals for facilities and infrastructure, c) conducting training and technical guidance, and d) repairing servers on the Telunjuk Sakti application. Keywords: Telunjuk Sakti Application, Administrative Services, Information Technology